2022
DOI: 10.3389/fnut.2022.910094
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence of Health Risks From Exposure to Micro- and Nanoplastics in Foods?

Abstract: The human health impact of exposure to micro (MP) and nanoplastics (NP) from food remains unknown. There are several gaps in knowledge that prevent a complete risk assessment of them. First, the fact that some plastics may be chemically harmful, either directly toxic themselves or because they absorb and carry other components, which makes these particles may possess 3 types of hazards, physical, chemical and biological. In addition, the levels at which toxic effects may occur are unknown and there is a lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
10
0
2
Order By: Relevance
“…Among other biological molecules in the environment, it is likely that MPs can act as carriers for antigens and allergens and, upon inhalation or ingestion, induce an immune reaction that differs from the reaction induced by isolated antigens/allergens. Moreover, it has been established that exposure to MPs can induce an inflammatory reaction and barrier impairment in the digestive system and lungs, thereby exacerbating pathological reactions to food and inhaled allergens [ 41 , 42 ]. In the case of dermal contact, exposure may occur through contaminated soil, settled dust, textiles, and cosmetics [ 16 , 17 , 43 , 44 , 45 , 46 ].…”
Section: Interactions Between Microorganisms and Microplasticsmentioning
confidence: 99%
“…Among other biological molecules in the environment, it is likely that MPs can act as carriers for antigens and allergens and, upon inhalation or ingestion, induce an immune reaction that differs from the reaction induced by isolated antigens/allergens. Moreover, it has been established that exposure to MPs can induce an inflammatory reaction and barrier impairment in the digestive system and lungs, thereby exacerbating pathological reactions to food and inhaled allergens [ 41 , 42 ]. In the case of dermal contact, exposure may occur through contaminated soil, settled dust, textiles, and cosmetics [ 16 , 17 , 43 , 44 , 45 , 46 ].…”
Section: Interactions Between Microorganisms and Microplasticsmentioning
confidence: 99%
“…Interestingly, most of the damage caused by MPs on the intestinal barrier seem to be more directly dependent on the particle size and not so much on their composition ( 163 , 164 ). Altogether, these data point towards a potential contribution of MPs to allergic diseases development due to the deleterious effect on the gut epithelium and their pro-inflammatory potential ( 68 , 165 ); nevertheless, further research is required to clarify MP effects in human health.…”
Section: Diet Modulates Epithelial Integrity: Protective and Harmful ...mentioning
confidence: 99%
“…Approximately 200 of the hundreds of thousands allergenic proteins have been isolated from food [ 13 ] and include peanuts, soybeans, crustacea, fish, cow’s milk, eggs, tree nuts and wheat. According to Hefle et al [ 14 ] these allergens make 90% of all reported food allergies worldwide [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Risk Factors and Links Between Allergy Epidemiology And Immu...mentioning
confidence: 99%
“…This anti-inflammatory activity can be explained by the presence of active flavonoids and cinnamic acid derivatives [ 119 , 120 , 135 , 136 , 137 , 138 ]. The former include acacetin, quercetin, and naringenin (terpenoid constituents may exert an addictive effect; the latter include CAPE and CA [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ,…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%